Bioresource management and climate change - Indian Science Congress 2008 : Shillong, India); Kumar, Dilip, Dr.; Rajendran, K. V., 1962-; Jahageerdar, S. (Shrinivas) (New Delhi : Studium Press (India), 2011)
Papers presented at the 96th Indian Science Congress, held at Shillong in December 2008.
Includes bibliographical references and index.
Keywords: Biodiversity -- Climatic factors -- India -- Congresses; Biodiversity conservation -- India -- Congresses